Research on the double-edged sword effect of AI in middle school students’ learning applications - Liu Yuxing (SHS Web of Conferences)
Middle school children frequently utilize AI to help them learn, but this has both beneficial and harmful consequences. This study used a questionnaire survey method to investigate the AI application among 129 students in order to explore the double-edged sword effect of AI in middle school students’ learning. The research results indicate that AI’s application breadth involves answering questions, searching for information, editing texts, and building text frameworks; In terms of application depth, middle school students use AI as a supplement to their abilities. The positive effects of AI in middle school students’ learning mainly include improving efficiency, finding problem directions, answering questions, and expanding depth; The negative effects mainly include plagiarism of artificial intelligence, cultivation of lazy psychology, ability degradation, and excessive dependence. The breadth and depth of AI application in middle school students have little impact on the positive effects; The age of middle school students, as well as the fact that they have never used, supplemented their abilities, and plagiarized artificial intelligence, all have a significant impact on negative effects. Finally, based on the research findings, this study provides targeted recommendations for future research.